THE ROLE OF RAILWAY TRANSPORT OF UKRAINE IN ENSURING A WELL-ESTABLISHED DEVELOPMENT SOCIETY - Barash, Yu. S.; Korzhenevych, I. P. (Science and Transport Progress, 2008)
The railway transport ofUkraineis examined from positions of the sustainable development.